Improvement of Science Learning Outcomes on the Topic of Changes in the State of Matter Thru the Game-Based Learning Model Assisted by Wordwall Media for 3rd Grade Elementary School - Insyiatul Iftitah; Lasim Muzammil; Qomariyah (Journal of Practice Learning and Educational Development, 2026)
This research is motivated by the low learning outcomes of students in the IPAS subject on the material of changes in the state of matter in the third grade of elementary school. The aim of this research is to improve students' learning outcomes thru the application of the Game Based Learning model assisted by Wordwall media. This research is a Classroom Action Research (CAR) conducted in two cycles, with 28 third-grade elementary school students as the research subjects. Each cycle consists of the stages of planning, implementation, observation, and reflection. The data collection techniques used are tests, observations, and documentation. Data were analyzed descriptively, both quantitatively and qualitatively. The research results show that the application of the Game Based Learning model assisted by Wordwall media can improve students' learning outcomes. This is evidenced by the increase in the average class score from 58.07 in the pre-cycle to 68.50 in cycle I and further increasing to 81.14 in cycle II. The percentage of learning completeness also improved from 32.14% in the pre-cycle to 53.57% in cycle I and 82.14% in cycle II. Additionally, the N-Gain calculation result of 0.55 falls into the moderate category. Thus, it can be concluded that the application of the Game Based Learning model assisted by Wordwall media can improve the learning outcomes of IPAS on the material of the change of state of matter for third-grade elementary school students.